Economic dynamics : phase diagrams and their economic application - Shone, Ronald (Cambridge University Press, 2002)
"This is the substantially revised and restructured second edition of Ron Shone's successful undergraduate and graduate textbook Economic Dynamics." "The book provides detailed coverage of dynamics and phase diagrams including: quantitative and qualitative dynamic systems, continuous and discrete dynamics, linear and nonlinear systems and single equation and systems of equations. It illustrates dynamic systems using Mathematica, Maple and spreadsheets. It provides a thorough introduction to phase diagrams and their economic application and explains the nature of saddle path solutions."--Jacket